| radical 3 - radical 5 | + | radical 3 + radical 5 | - | 3-2 radical 5 |
Răspunsuri la întrebare
Răspuns de
1
Răspuns:
3
Explicație pas cu pas:
radical 3 - radical 5 <0 (pt ca √3 < √5 )
⇒ |√3 - √5 | = √5 -√3
radical 3 + radical 5 >0
⇒ |√3 + √5 | = √3 + √5
3-2 radical 5 < 0 (pt ca 3< 2*√5 )
⇒ | 3-2 radical 5 | = 2√5 -3
------------------------------------------
(√5 -√3 )+(√3 +√5) - (2√5 - 3) =
2√5 -2√5 +3 =
3
Alte întrebări interesante
Matematică,
8 ani în urmă
Limba română,
8 ani în urmă
Matematică,
8 ani în urmă
Engleza,
8 ani în urmă
Fizică,
8 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă